Giant, calcified colloid cyst of the lateral ventricle. (February 2016) - Two, Aimee; Christian, Eisha; Mathew, Anna; Giannotta, Steven; Zada, Gabriel
Highlights: Giant, calcified cystic mass is a rare presentations of colloid cyst. We present a patient with a 5cm calcified mass arising within the lateral ventricle. Colloid cysts should be in the differential diagnosis of any calcified, cystic, intraventricular mass. Abstract: We report a patient with a giant, calcified colloid cyst in the left lateral ventricle. Colloid cysts are slow growing, benign lesions, commonly originating in the roof of the anterior third ventricle near the foramen of Monro. Many colloid cysts are small lesions which are either discovered incidentally or cause headache, visual changes, memory deficits, and/or syncope. Giant colloid cysts are rare. A 40-year-old man presented with a month long history of worsening headaches and was found to have a multiloculated 5 cm intraventricular mass with an anterior hyperdensity, suggestive of calcification, arising within the lateral ventricles. He underwent an interhemispheric transcallosal approach for resection of the mass. The pathology was consistent with a giant colloid cyst with calcification in the anterior cyst wall. Giant, calcified mass is a rare presentation of colloid cyst. Although rare, this diagnosis remains an important consideration in the differential diagnosis of any calcified, cystic intraventricular mass.